2020
DOI: 10.3390/antiox9090788
|View full text |Cite
|
Sign up to set email alerts
|

Cudratricusxanthone O Inhibits H2O2-Induced Cell Damage by Activating Nrf2/HO-1 Pathway in Human Chondrocytes

Abstract: Osteoarthritis (OA) is a common joint degenerative disease induced by oxidative stress in chondrocytes. Although induced-heme oxygenase-1 (HO-1) has been found to protect cells against oxygen radical damage, little information is available regarding the use of bioactive compounds from natural sources for regulating the HO-1 pathway to treat OA. In this study, we explored the inhibitory effects of cudratricusxanthone O (CTO) isolated from the Maclura tricuspidata Bureau (Moraceae) on H2O2-induced damage of SW13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 35 publications
(31 reference statements)
1
21
0
Order By: Relevance
“…These changes were accompanied by an increase in 8-isoprostane F2-α levels but a lower level of intracellular TNF-α. Previous studies showed that the IC 50 values of H 2 O 2 in SW1353 chondrocytes ranged from 0.5 to 1 mM upon 1 h to 24 h of treatment [ 15 , 37 , 38 , 39 ], while IC 50 values around 5–8.26 µM for MIA were reported for SW1353 chondrocytes [ 16 , 43 ] and primary chondrocytes [ 17 , 46 , 87 ]. Our data demonstrated that IC 50 values of H 2 O 2 and MIA were 82.5 µM (6- to 12-fold lower) and 31.5 µM (4- to 6-fold higher), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These changes were accompanied by an increase in 8-isoprostane F2-α levels but a lower level of intracellular TNF-α. Previous studies showed that the IC 50 values of H 2 O 2 in SW1353 chondrocytes ranged from 0.5 to 1 mM upon 1 h to 24 h of treatment [ 15 , 37 , 38 , 39 ], while IC 50 values around 5–8.26 µM for MIA were reported for SW1353 chondrocytes [ 16 , 43 ] and primary chondrocytes [ 17 , 46 , 87 ]. Our data demonstrated that IC 50 values of H 2 O 2 and MIA were 82.5 µM (6- to 12-fold lower) and 31.5 µM (4- to 6-fold higher), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The use of commercially available chondrocyte cell lines could overcome these limitations because they are readily available, cost-effective, technically less challenging to culture and without significant ethical issues compared with primary chondrocytes. Several human chondrocyte cell lines have been used as in vitro OA models, including SW1353 chondrocytes [ 15 , 16 , 17 ], CHON-001 cells [ 18 , 19 ], CHON-002 cells [ 20 ], and C-28/I2, T/C-28a2 and T/C-28a4 chondrocytes [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Osteoarthritis (OA) is a common joint degenerative disease induced by oxidative stress in chondrocytes. Kim et al [ 6 ] demonstrated the inhibitory effects of cudratricusxanthone O (CTO), isolated from the Maclura tricuspidata Bureau (Moraceae), on the H 2 O 2 -induced damage of SW1353 chondrocytes. CTO induced HO-1 expression, involving the translocation of Nrf2 into the nucleus.…”
mentioning
confidence: 99%